A Benzofuranone from the Flowers of Nyctanthes arbortristis and its Antibacterial and Cytotoxic Activities - Khatune, Naznin Ara; Mossadik, M Asik; Rahman, M Mukhlesur; Khondkar, Proma; Haque, M Ekramul; Gray, Alexander I (Dhaka University Journal of Pharmaceutical Sciences, 2007)
A benzofuranone, 3,3a,7,7a-tetrahydro-3a-hydroxy-6(2H)-benzofuranone (1), was isolated from the flower of Nyctanthes arbortristis Linn. The compound was identified by 1D and 2D NMR and MS analyses. It showed significant antibacterial activity against both Gram positive and Gram negative bacteria. The LC50 of the compound was found to be 8.73 mg/ml in brine shrimp lethality bioassay. Key words: Nyctanthes arbortristis, Nyctantheceae; 3,3a,7,7a-tetrahydro-3a-hydroxy-6(2H)-benzofuranone, Antibacterial, Cytotoxicity Dhaka Univ. J. Pharm. Sci. Vol.4(1) 2005 The full text is of this article is available at the Dhaka Univ. J. Pharm. Sci. website